A Situation Awareness Model of System Survivability Based on Variable Fuzzy Set - Jinhui Zhao; Yu Zhou; Liangxun Shuo (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Because of the complexities and diversities of security alerts in modern networks, it is extremely difficult to precisely analyze and evaluate the survival situation. After analyzed the research progress of survival situation awareness, a hierarchical model of survival situational awareness is proposed, based on fusion technology of variable fuzzy set. In order to improve the discrimination of features, the efficient light-computation fusion mechanisms are employed to preproccess the multi-source data. Subsequently, the situation assessment adopted fusion technology of variable fuzzy set theory to improve the accuracy and objectivity of evaluation results. Finally, time series of services or hosts are introduced to judge the survival status and predict the trends by fuzzy reasoning. Experiments indicate that proposed model is suitable for a real network environment, and the perception results more scientific and accurate, which is valuable for generalizations and applications. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1691